A Socio-Psychological Model of Urban Millennial Postgraduate Students’ Votes: Indonesia 2014 and 2019 Presidential Elections - Erawaty, Dyah Permana; Salamah, Ummi (UI Scholars Hub, 2021)
The 2019 presidential election showed many swing voters between the candidates who battled for the second time. This study seeks to understand the cause behind voters’ decisions to switch their voters and how millennial voters with postgraduate education backgrounds swing their votes. This study treats the votes cast by urban millennial postgraduate students as its unit of analysis. Additionally, it aims to find out whether social media has contribution to switch votes. We employed the Columbian and Michigan approach to the socio-psychological model as our conceptual framework and incorporated a modification of the concept of mass self-communication, which includes the immersion of mass communication into interpersonal communication. This study was carried out under a qualitative post-positivist paradigm and used a single holistic case study research method. This study uses pattern-matching logic analysis techniques. The results show that millennial voters swung their votes in the 2019 presidential election because of social variables, namely religion, ethnicity, and family relations. On the psychological variables, we found no role played by party identification but instead an evaluation of candidates, such as incumbent performance and identity coherence, and issue orientation, particularly about human rights and women’s issues. We also found that voters’ decision-making process was influenced by political memes, which played a role as a gate to further social group discussions and motivation to learn more about the candidates’ identities. Additionally, presidential debates’ presentation of candidates’ debating skills contributed to voting decisions. Mass self-communication, particularly on social media, was not done concerning politics as voters did not want their political affiliation to be known by other internet users.